0
$\begingroup$

Let $z_1,z_2,z_3\in\mathbb{C}$ such that $|z_1|=|z_2|=|z_3|=1, z_1+z_2+z_3=1$. Calculate $z_1^{2003}+z_2^{2003}+z_3^{2003}.$

Let's say $S_k=z_1^k+z_2^k+z_3^k$. I tried calculating $S_2,S_3,S_4,S_6$ so maybe I see a pattern.

$|z|=1\Leftrightarrow \bar{z}=\frac{1}{z}.~z_1+z_2+z_3=1\Rightarrow \bar{z_1}+\bar{z_2}+\bar{z_3}=1\Rightarrow \frac{1}{z_1}+\frac{1}{z_2}+\frac{1}{z_3}=1\Rightarrow \mathbf{z_1z_2+z_1z_3+z_2z_3=z_1z_2z_3}.$

Also $z_1+z_2+z_3=1\Rightarrow (z_1+z_2+z_3)^2=1\Rightarrow \underbrace{z_1^2+z_2^2+z_3^2}_{S_2}+2\underbrace{(z_1z_2+z_1z_3+z_2z_3)}_{z_1z_2z_3}=1$ $\Rightarrow S_2+2z_1z_2z_3=1$

$\mathbf{\Rightarrow S_2=1-2z_1z_2z_3}$

$S_3=z_1^3+z_2^3+z_3^3=\underbrace{(z_1+z_2+z_3)}_1\big(\underbrace{z_1^2+z_2^2+z_3^2}_{S_2}-\underbrace{(z_1z_2+z_1z_3+z_2z_3)}_{z_1z_2z_3}\big)+3z_1z_2z_3$

$S_3=S_2-z_1z_2z_3+3z_1z_2z_3=S_2+2z_1z_2z_3\Rightarrow \mathbf{S_3=1}$

I will calculate an identity we will need for $S_4$:

$z_1z_2+z_1z_3+z_2z_3=z_1z_2z_3\Rightarrow (z_1z_2+z_1z_3+z_2z_3)^2=(z_1z_2z_3)^2$

$\Rightarrow (z_1z_2)^2+(z_1z_3)^2+(z_2z_3)^2+2z_1z_2z_3\underbrace{(z_1+z_2+z_3)}_1=(z_1z_2z_3)^2$

$\Rightarrow\mathbf{(z_1z_2)^2+(z_1z_3)^2+(z_2z_3)^2=(z_1z_2z_3)^2-2z_1z_2z_3}$

$S_4=z_1^4+z_2^4+z_3^4={\underbrace{(z_1^2+z_2^2+z_3^2)}_{S_2}}^2-2\underbrace{((z_1z_2)^2+(z_1z_3)^2+(z_1z_3)^2)}_{(z_1z_2z_3)^2-2z_1z_2z_3}$

$S_4=(1-2z_1z_2z_3)^2-2\big((z_1z_2z_3)^2-2z_1z_2z_3\big)=4(z_1z_2z_3)^2-4z_1z_2z_3+1-2(z_1z_2z_3)^2+4z_1z_2z_3$ $\Rightarrow \mathbf{S_4=1+2(z_1z_2z_3)^2}$

$S_6=z_1^6+z_2^6+z_3^6={\underbrace{(z_1^3+z_2^3+z_3^3)}_{S_3=1}}^2-2\big((z_1z_2)^3+(z_1z_3)^3+(z_2z_3)^3\big)$

$(z_1z_2)^3+(z_1z_3)^3+(z_2z_3)^3=$

$=\underbrace{(z_1z_2+z_1z_3+z_2z_3)}_{z_1z_2z_3}\big(\underbrace{(z_1z_2)^2+(z_1z_3)^2+(z_2z_3)^2}_{(z_1z_2z_3)^2-2z_1z_2z_3}-\underbrace{(z_1z_2+z_1z_3+z_2z_3)}_{z_1z_2z_3}\big)+3(z_1z_2z_3)^2$

$=z_1z_2z_3\big((z_1z_2z_3)^2-3z_1z_2z_3\big)+3(z_1z_2z_3)^2=(z_1z_2z_3)^2(z_1z_2z_3-3)+(z_1z_2z_3)^2\cdot3=(z_1z_2z_3)^3$

$\mathbf{S_6=1-2(z_1z_2z_3)^3}$

Let's take a look on $S_k$ for $k$ even.

$ \begin{cases} S_0=1+2(z_1z_2z_3)^0 \\ S_2=1-2(z_1z_2z_3)^1 \\ S_4=1+2(z_1z_2z_3)^2 \\ S_6=1-2(z_1z_2z_3)^3 \end{cases} $

And for $k$ odd we have $S_1=S_3=1$.

I don't think it's a coincidence.

My hypothesis:

$ S_k= \begin{cases} 1+2(-z_1z_2z_3)^\frac{k}{2}&k\text{ even} \\ 1&k\text{ odd} \end{cases} $

So the answer would be $S_{2013}=1$ which, judging by the answers that are given at the back of the textbook, is correct.

The question is, why is that? Can anyone prove it by any means? I thought of induction but I couldn't solve it.

EDIT:

I've just calculated $S_8$ and it is $1+2(z_1z_2z_3)^4$.

Also $(z_1z_2)^4+(z_1z_3)^4+(z_2z_3)^4=(z_1z_2z_3)^4+2(z_1z_2z_3)^2$.

$\endgroup$
7
  • $\begingroup$ You could mention your question as a generalization of the issue asked some hours ago here $\endgroup$
    – Jean Marie
    Jun 24 at 13:40
  • $\begingroup$ @JeanMarie Nope, there we had $z_1^2+z_2^2+z_3^2=0$, or am I missing something? $\endgroup$
    – Neox
    Jun 24 at 13:41
  • $\begingroup$ You are right... $\endgroup$
    – Jean Marie
    Jun 24 at 13:42
  • $\begingroup$ @JeanMarie And btw I figured out how to solve that one. $\endgroup$
    – Neox
    Jun 24 at 13:43
  • $\begingroup$ It looks a maths Olympiad subject. Right ? $\endgroup$
    – Jean Marie
    Jun 24 at 13:44
2
$\begingroup$

Consider the cubic polynmomial with $z_1,z_2,z_3$ as its only roots, id est the polynomial $$(x-z_1)(x-z_2)(x-z_3)=x^3-(z_1+z_2+z_3)x^2+(z_1z_2+z_2z_3+z_1z_3)x-z_1z_2z_3=x^3-x^2+z_1z_2z_3x-z_1z_2z_3$$ using the fact that you proved above $z_1z_2+z_2z_3+z_1z_3=z_1z_2z_3$. For the sake of simplicity we assume $z_1z_2z_3=a$. then our equation is $x^3-x^2+ax-a=0$ which is satisfied by $z_1,z_2,z_3$, so they must also satisfy $x^m=x^{m-1}-ax^{m-2}+ax^{m-3}$, on adding these equations for $z_1,z_2,z_3$, we get that $$S_m=S_{m-1}-aS_{m-2}+aS_{m-3} \implies S_m-S_{m-1}=-a(S_{m-2}-S_{m-3})\implies \frac{S_m-S_{m-1}}{S_{m-2}-S_{m-3}}=-a$$ Let's call this equation $f(m)$. For $m$ even, multiplying equations $f(m),f(m-2),\cdots , f(4)$, we get $$\frac{S_m-S_{m-1}}{S_2-S_1}=(-a)^{\frac{m}{2}-1}\implies S_{m}-S_{m-1}=(-a)^{\frac{m}{2}-1}(-2a)=2(-a)^{\frac{m}{2}}$$ using the values of $S_2$ calculated by you. Similarly for odd $m$, $$S_m-S_{m-1}=-2(-a)^{\frac{m-1}{2}}$$ therefore for even $m$, we write $$S_{m}-S_{m-1}=2(-a)^{\frac{m}{2}}$$ $$S_{m-1}-S_{m-2}=-2(-a)^{\frac{m-2}{2}}$$ upto $$S_2-S_1=2(-a)$$ Add all these up and we get $$S_m-S_1=2(-a)^{\frac{m}{2}}\implies S_m=1+2(-a)^{\frac{m}{2}}$$ which is what you have hypothesized. Similar work will let you to the value of $S_m$ for odd $m$ which is indeed $1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.